The complementarity between calls and messages in mobile telephony - Grzybowski, L.; Pereira, P. (Information Economics and Policy, 2008)
This article estimates price elasticities of demand for mobile telephone calls and messages. We use panel data consisting of telephone bills to Portuguese mobile telephony consumers. In order to account for the unobserved individual heterogeneity and data censoring, we estimate a Tobit model for panel data with individual random effects. The demands for calls and messages are inelastic. Calls and messages are found to be complements.